Differences in Norovirus-Associated Hospital Visits Between Jewish and Bedouin Children in Southern Israel. Issue 9 (September 2015) - Leshem, Eyal; Givon-Lavi, Noga; Vinjé, Jan; Gregoricus, Nicole; Parashar, Umesh; Dagan, Ron
Abstract : Population-based surveillance during 2006–2013 showed that norovirus hospitalization rates among Bedouin (low-middle income settings) children <5 years old were 13.9/10, 000 person-years compared with 7.1/10, 000 among Jewish (high-income settings) children who were <5 years (rate ratio: 2.0, 95% confidence interval: 1.6–2.3). Differences were most prominent among infants (59.7 vs. 19.7/10, 000, respectively; rate ratio: 3.0, 95% confidence interval: 2.5–3.8). GII.3 and GII.4 strains dominated (67%) in both populations. Abstract : Supplemental Digital Content is available in the text.